New Method and Tool for TEM Samples Preparation - Boguslavsky, D.; Cherepin, V.; Polubotko, Y.; Smith, C. (Металлофизика и новейшие технологии, 2013)
А new tool for TEM sample preparation, which allows preparing a thin lamella with thickness less than 20 nm surrounded by and embedded in bulk material, is presented. The main advantages of this system are low ion milling induced damage (less than 2 nm in depth), low process time (1—2 hours), in situ sample monitoring during ion milling (topography and sample thickness), and large treated area (5—30 μm along the area of interest). Comparison of few kinds of working substance of ion sources as well as schemes or drawings of key components of the tool are presented.